Improving Hospital's Legal Responsibility in Drug and Medical Device Management - Widjaja, Gunawan; Dhanudibroto, Handojo (Lafadz Jaya Publisher, 2025)
Increasing the legal responsibility of hospitals in the management of drugs and medical devices is a strategic step in improving the quality of health services and protecting patient rights. Hospitals have an obligation to ensure that all drugs and medical devices used meet the standards of safety, effectiveness, and compliance with applicable regulations. Good governance includes distribution supervision, stock management, and usage control, which serve to minimise risks to patients. In addition, improper management can potentially lead to legal consequences in the form of sanctions or prosecution. Overall, strengthening the legal responsibility of hospitals is an important element in creating a safer, more efficient and reliable healthcare system in accordance with regulatory standards and medical ethics.